Biofilm forming ability of intermediate and saprophytic Leptospira on abiotic and biotic surfaces - Kasing, Apun; Jennifer, Jalan; Chai, Fung Pui; Lesley Maurice, Bilung; Hashimatul Fatma, Hashim; Anisa Aina Nadiah, Md Ahsan; Rennielyn, Rupert (Malaysian Society for Microbiology, 2018)
Aims: Leptospira spp. has the ability to develop biofilm communities and this attribute is an essential factor to leptospiral pathogenesis. This study aims to assess and quantify the biofilm forming ability of intermediate and saprophytic Leptospira strains. Methodology and results: The biofilm assay was quantified on microtitre polystyrene plates (abiotic) and wood chips (Jelutong Paya hardwood) over a duration of 11 days. Phase contrast light microscope was used to assess the structure of the on the surface. The biofilm production on wood chips surface were approximately one times higher than on polystyrene plate surface indicating Leptospira strains were capable of forming higher quantity of biofilm on biotic surface compared to abiotic surface by both intermediate and saprophytic Leptospira. A significant difference (p<0.05) exists in biofilms produced by Leptospira on wood surface which formed more biofilm than on polystyrene surface. The strongest biofilm producer is intermediate strain G14 with OD600 of 2.283±0.180 and OD600 of 2.333±0.037, on polystyrene and wood surface, respectively. Visualisation of biofilm by phase-contrast microscopy of two representative strains correlated with the OD values and the colour intensity of stained microtitre plates and wood surfaces. The biofilm formed comprises of a three-step process are adherence (1th to 24th h), maturation (6th to 7th day) and detachment (9th to 11th day) of biofilms. Conclusion, significance and impact of study: The contact time of intermediate pathogenic strains was faster compared to saprophytic strain, indicating the biofilm forming ability is related to the level of pathogenicity of Leptospira strains.